2012
DOI: 10.1038/nchem.1234
|View full text |Cite
|
Sign up to set email alerts
|

Optochemical control of genetically engineered neuronal nicotinic acetylcholine receptors

Abstract: Advances in synthetic chemistry, structural biology, molecular modelling and molecular cloning have enabled the systematic functional manipulation of transmembrane proteins. By combining genetically manipulated proteins with light-sensitive ligands, innately ‘blind’ neurobiological receptors can be converted into photoreceptors, which allows them to be photoregulated with high spatiotemporal precision. Here, we present the optochemical control of neuronal nicotinic acetylcholine receptors (nAChRs) with photosw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 50 publications
(69 reference statements)
4
139
0
3
Order By: Relevance
“…More importantly, optogating relies on the possibility that receptors can be activated by light even if important biologically active or regulatory sites were genetically modified. This feature sharply contrasts with other optically controlled ligand-gated channels, such as glutamate (LiGluR) (5), GABA A (10), and nicotinic receptors (LinAChR) (6) in which endogenous neurotransmitters can still activate engineered receptors. Optogating thus provides a unique opportunity to study in native tissues the specific contribution of light-mediated signaling that is not imbalanced by the endogenous stimulus.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…More importantly, optogating relies on the possibility that receptors can be activated by light even if important biologically active or regulatory sites were genetically modified. This feature sharply contrasts with other optically controlled ligand-gated channels, such as glutamate (LiGluR) (5), GABA A (10), and nicotinic receptors (LinAChR) (6) in which endogenous neurotransmitters can still activate engineered receptors. Optogating thus provides a unique opportunity to study in native tissues the specific contribution of light-mediated signaling that is not imbalanced by the endogenous stimulus.…”
Section: Discussionmentioning
confidence: 74%
“…2C). These persistent effects demonstrate bistability of the optogating method, a key feature that was already observed for other receptors (6,24); it allows tethered azobenzenes to remain in the dark either in their cis or trans isomer following brief illuminations. These data establish a stable photocontrol of channels.…”
Section: Resultsmentioning
confidence: 99%
“…One promising alternative to microbial opsins is an optopharmacological strategy that uses synthetic azobenzene-based photoswitches to endow light sensitivity either to native ion channels of neurons (17,18) or to engineered mammalian receptors and channels that, like the microbial opsins, allow for genetic targeting to specific cells (19)(20)(21)(22). We previously showed that an engineered light-gated ionotropic glutamate receptor (LiGluR) restores light responses to blind retina degeneration (rd1) mice (23).…”
Section: Significancementioning
confidence: 99%
“…The increase in our knowledge of molecular and atomic structure of ligand-gated channels over the past 10 years has allowed one such approach (photoswitchable tethered ligands) to become much more sophisticated, because cysteines can be introduced into the channel protein exactly where required to form an attachment point. The method has been applied to pentameric nicotinic receptors (6) and tetrameric glutamate receptors (7,8). Although attaching ligands through photoswitchable tethers is proving extremely valuable, an intimate structural knowledge of a closed and open state of a channel also allows for optical control of conformation at parts of the protein that are remote from the agonist binding site (9)(10)(11) 16).…”
mentioning
confidence: 99%